2004
DOI: 10.1101/gad.1256804
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mTOR function in response to hypoxia by REDD1 and the TSC1/TSC2 tumor suppressor complex

Abstract: Mammalian target of rapamycin (mTOR) is a central regulator of protein synthesis whose activity is[Keywords: Tuberous Sclerosis Complex; TSC1; TSC2; REDD1/RTP801; mTOR; Hypoxia] Supplemental material is available at http://www.genesdev.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
1,110
8
11

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,227 publications
(1,163 citation statements)
references
References 53 publications
(95 reference statements)
34
1,110
8
11
Order By: Relevance
“…It is well established that HIF1a promotes carcinogenesis by various mechanisms, including the enhancement of tumor angiogenesis, invasion, metastasis and resistance to therapy (Semenza, 2003;Bertout et al, 2008). Our observation that HIF1a inhibits ALK þ TCL cell proliferation by partially inhibiting mTORC1 activation is in agreement with the previous finding that HIF1a inhibits TOR in Drosophila by activating the REDD analog protein (Brugarolas et al, 2004). This induced, mTORC1-dependent relative cell quiescence combined with the simultaneous fostering by HIF1a of the VEGF synthesis (Figure 4d) indicates that under suboptimal, hypoxic conditions, HIF1a adjusts the growth rate of ALK þ TCL cells and promotes blood vessel formation to increase oxygen supply and, ultimately, optimizes conditions for an undisturbed tumor expansion.…”
Section: Npm/alk-stat3 Pathway Induces Hif1a Expression M Marzec Et Alsupporting
confidence: 93%
“…It is well established that HIF1a promotes carcinogenesis by various mechanisms, including the enhancement of tumor angiogenesis, invasion, metastasis and resistance to therapy (Semenza, 2003;Bertout et al, 2008). Our observation that HIF1a inhibits ALK þ TCL cell proliferation by partially inhibiting mTORC1 activation is in agreement with the previous finding that HIF1a inhibits TOR in Drosophila by activating the REDD analog protein (Brugarolas et al, 2004). This induced, mTORC1-dependent relative cell quiescence combined with the simultaneous fostering by HIF1a of the VEGF synthesis (Figure 4d) indicates that under suboptimal, hypoxic conditions, HIF1a adjusts the growth rate of ALK þ TCL cells and promotes blood vessel formation to increase oxygen supply and, ultimately, optimizes conditions for an undisturbed tumor expansion.…”
Section: Npm/alk-stat3 Pathway Induces Hif1a Expression M Marzec Et Alsupporting
confidence: 93%
“…Many of these target genes have been found to form feedback loops via the regulation of the hypoxia-related activity of the mTOR pathway. These include REDD1 that has been reported to activate the Tuberous Sclerosis Complex 1/2 (TSC1/2) [75]. The TSC1/2 possesses GTPase activating function that renders the mTOR activator RHEB inactive [76].…”
Section: Crosstalk Between the Hif And Other Regulatory Pathwaysmentioning
confidence: 99%
“…The control of mTORC2 activity is not well understood, but one study suggested that Rheb-GTP, the activator of mTORC1, inhibits mTORC2 (REF. 34). If this is the case, then how are both mTORC1 and mTORC2 activated during infection with viruses such as HCMV?…”
Section: The Poxviridaementioning
confidence: 99%